1998
DOI: 10.1021/la971271z
|View full text |Cite
|
Sign up to set email alerts
|

Some Stability Criteria for Double Emulsions

Abstract: Double W/O/W emulsions consist in an inverse emulsion which is dispersed within a water continuous phase as direct emulsion droplets. The aim of this paper is to explore the basic rules that govern the stability of double emulsions. By associating both water-and oil-soluble surfactants in various concentrations, we produce W/O/W double emulsions. We identify two types of instabilities that are responsible for the evolution of double emulsions: (i) coalescence of the small inner droplets with the globule interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 23 publications
4
154
1
Order By: Relevance
“…Double emulsions may be either of the water-in-oil-in-water type (W/O/W) (with dispersed oil drops containing smaller aqueous droplets) or of the oil-in-water-in-oil type (O/W/O) (with dispersed aqueous globules containing smaller oil dispersed droplets). [8] Liquid membrane extraction processes have certainly some attractive features like simple operation, high efficiency, extraction and stripping in one stage, larger interfacial area and scope of continuous operation. [9,10] In ELM mass transfer surface area to volume ratio is very high up to (1000 -3000m 2 /m 3 ) and internal surface area to volume ratio is also lager (106 m 2 /m 3 ).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 1 more Smart Citation
“…Double emulsions may be either of the water-in-oil-in-water type (W/O/W) (with dispersed oil drops containing smaller aqueous droplets) or of the oil-in-water-in-oil type (O/W/O) (with dispersed aqueous globules containing smaller oil dispersed droplets). [8] Liquid membrane extraction processes have certainly some attractive features like simple operation, high efficiency, extraction and stripping in one stage, larger interfacial area and scope of continuous operation. [9,10] In ELM mass transfer surface area to volume ratio is very high up to (1000 -3000m 2 /m 3 ) and internal surface area to volume ratio is also lager (106 m 2 /m 3 ).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…On the other hand, an overly stable emulsion causes problems during its settling and de-emulsification after it extracts the pollutants [12]. There are only a small number of investigations have been made on the stability of (W/O/W) Fig.1 Different Types of Emulsion [8] emulsion system in stirred vessels. [13] Instability of ELM results in their tendency to undergo swelling and internal phase leakage (breakage).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…There are several factors that affect the stability of emulsions, such as preparation methods, compound formulation, storage conditions, and so forth [47]. Here, we focused on storing double emulsions under different environments with the results shown in Figure 3a.…”
Section: Stability and Mass Transport Of Double Emulsionsmentioning
confidence: 99%
“…Although diffusion is the most important mechanism of transport in the multiple emulsion systems, there is evidence that ionized materials may pass across the oil layer. Kita et al [25] suggested that ionized drug along with water is mixed with micelles of hydrophilic and hydrophobic surfactants and cross the oil layer. Another possible transport mechanism is carrier mediated transport [26].…”
Section: Stabilitymentioning
confidence: 99%
“…For the multiple emulsion, while no liquefaction was observed in the samples kept at 8 o C (in refrigerator) and 25 o C (in oven) during 28 days, slight liquefaction was observed in the samples kept at 40 o C (in oven), 40 o C at 75% RH (in stability cabin) on 21st day. Liquefaction is the sign of instability; it may be attributed to the passage of water from the internal phase to external phase as described by many researchers [23,25].…”
Section: Liquefactionmentioning
confidence: 99%